Consultation on agricultural commodity price problems (FAO RomeIT, 2003)
Seeks to promote international action to deal with agricultural commodity price problems and to identify possible approaches to meeting the concerns of commodity sectors, particularly of developing countries and of poor farmers.
Keywords: AGRICULTURAL PRODUCTS